Efficacy and safety of lumacaftor/ivacaftor combination therapy in patients with cystic fibrosis homozygous for Phe508del CFTR by pulmonary function subgroup: a pooled analysis. Issue 8 (August 2016) - Elborn, J Stuart; Ramsey, Bonnie W; Boyle, Michael P; Konstan, Michael W; Huang, Xiaohong; Marigowda, Gautham; Waltz, David; Wainwright, Claire E; ,
Summary: Background: Lumacaftor/ivacaftor combination therapy has shown clinical benefits in patients with cystic fibrosis homozygous for the Phe508del CFTR mutation; however, pretreatment lung function is a confounding factor that potentially affects the efficacy and safety of this therapy. We aimed to assess the efficacy and safety of lumacaftor/ivacaftor therapy in these patients, defined by specific categories of lung function. Methods: Both trials (TRAFFIC and TRANSPORT) included in this pooled analysis were multinational, randomised, double-blind, placebo-controlled, parallel-group, phase 3 studies. Eligible patients from 187 participating centres in North America, Australia, and the European Union (both trials) were aged 12 years or older with a confirmed diagnosis of cystic fibrosis, homozygous for the Phe508del CFTR mutation, and with a percent predicted FEV1 (ppFEV1 ) of 40–90 at the time of screening. Patients were randomly assigned with an interactive web response system (1:1:1) to receive placebo, lumacaftor (600 mg once daily) plus ivacaftor (250 mg every 12 h), or lumacaftor (400 mg every 12 h) plus ivacaftor (250 mg every 12 h) for 24 weeks. Prespecified subgroup analyses of pooled efficacy and safety data by lung function, as measured by ppFEV1, were done for patients with baseline ppFEV1 (<40 and ≥40) and screening ppFEV1 (<70 and ≥70). The primary endpoint was the absolute change from baseline in ppFEV1 at week 24 analysed in all randomised patients who received at least one dose of study drug. Both trials are registered withClinicalTrials.gov (TRAFFIC:NCT01807923 ; TRANSPORT:NCT01807949 ). Findings: Both trials were done between April, 2013, and April, 2014. Of the 1108 patients included in the efficacy analysis, 81 patients had a ppFEV1 that decreased to lower than 40 between screening and baseline and 1016 had a ppFEV1 of 40 or higher at baseline. At screening, 730 had a ppFEV1 of less than 70, and 342 had a ppFEV1 of 70 or higher. Improvements in the absolute change from baseline at week 24 in ppFEV1 were observed with both lumacaftor/ivacaftor doses in the subgroup with baseline ppFEV1 levels lower than 40 (least-squares mean difference vs placebo was 3·7 percentage points [95% CI 0·5–6·9; p=0·024] in the lumacaftor [600 mg/day]–ivacaftor group and 3·3 percentage points [0·2–6·4; p=0·036] in the lumacaftor [400 mg/12 h]–ivacaftor group). Improvements in ppFEV1 compared with placebo were also reported in the subgroup with baseline ppFEV1 levels of 40 or higher (3·3 percentage points [2·3–4·4; p<0·0001] in the lumacaftor [600 mg per day]–ivacaftor group and 2·8 percentage points [1·7–3·8; p<0·0001] in the lumacaftor [400 mg/12 h]–ivacaftor group). Similar absolute improvements in ppFEV1 compared with placebo were observed in subgroups with screening ppFEV1 levels lower than 70 and ppFEV1 levels of 70 or higher. Increases in body-mass index and reduction in number of pulmonary exacerbation events were observed in both lumacaftor/ivacaftor dose groups compared with placebo across all lung function subgroups. Treatment was generally well tolerated, although the incidence of some respiratory adverse events was higher with lumacaftor/ivacaftor than with placebo in all subgroups. In patients with baseline ppFEV1 levels lower than 40, these adverse events included cough, dyspnoea, and abnormal respiration. Interpretation: These analyses confirm that lumacaftor/ivacaftor combination therapy benefits patients with cystic fibrosis homozygous for Phe508del CFTR who have varying degrees of lung function impairment. Funding: Vertex Pharmaceuticals.